Association of CD40 with rheumatoid arthritis confirmed in a large UK case-control study. Issue 5 (11th May 2009) - Orozco, Gisela; Eyre, Steve; Hinks, Anne; Ke, Xiayi; Wilson, Anthony G; Bax, Deborah E; Morgan, Ann W; Emery, Paul; Steer, Sophia; Hocking, Lynne; Reid, David M; et al.
Abstract : Objective: A recent meta-analysis of published genome-wide association studies (GWAS) in populations of European descent reported novel associations of markers mapping to the CD40, CCL21 and CDK6 genes with rheumatoid arthritis (RA) susceptibility while a large-scale, case-control association study in a Japanese population identified association with multiple single nucleotide polymorphisms (SNPs) in the CD244 gene. The aim of the current study was to validate these potential RA susceptibility markers in a UK population. Methods: A total of 4 SNPs (rs4810485 in CD40, rs2812378 in CCL21, rs42041 in CDK6 and rs6682654 in CD244 ) were genotyped in a UK cohort comprising 3962 UK patients with RA and 3531 healthy controls using the Sequenom iPlex platform. Genotype counts in patients and controls were analysed with the χ 2 test using Stata. Results: Association to the CD40 gene was robustly replicated (p=2×10 −4, OR 0.86, 95% CI 0.79 to 0.93) and modest evidence was found for association with the CCL21 locus (p=0.04, OR 1.08, 95% CI 1.01 to 1.16). However, there was no evidence for association of rs42041 ( CDK6 ) and rs6682654 ( CD244 ) with RA susceptibility in this UK population. Following a meta-analysis including the original data, association to CD40 was confirmed (p=7.8×10 −8, OR 0.87 (95% CI 0.83 to 0.92). Conclusion: In this large UK cohort, strong association of the CD40 gene with susceptibility to RA was found, and weaker evidence for association with RA in the CCL21 locus.